Tingkat Pengetahuan Mahasiswa Profesi Ners Angkatan 25 Universitas Muhammadiyah Surakarta tentang Penyakit HIV/AIDS - Dhimas Lanang Wicaksono; Adisty Rose Artistin (Journal of Telenursing (JOTING), 2023)
This study aims to describe the level of knowledge of class 25 nursing professional students at Muhammadiyah University of Surakarta regarding HIV/AIDS. The method used is descriptive research with a survey research design. The research results showed that of the 95 respondents, 65 people had a good level of knowledge (68.4%), 27 people had a sufficient level of expertise (28.4%), and three people had a poor level of understanding (3.2%). In conclusion, most students of the 25th batch of nursing profession students at Muhammadiyah University of Surakarta regarding HIV/AIDS have good knowledge. Keywords: HIV/AIDS, Students, Knowledge